Computing the time evolution of the apparent viscoelastic/viscoplastic Poisson's ratio of hydrating cement paste. (February 2015) - Li, X.; Grasley, Z.C.; Bullard, J.W.; Garboczi, E.J.
Abstract: A computational model has been developed that combines finite element methods with microstructure development simulations to quantitatively predict the viscoelastic/viscoplastic relaxation of cement paste due to intrinsic calcium silicate hydrate viscoelasticity/viscoplasticity and cement grain dissolution associated with the hydration process. The viscoelastic/viscoplastic Poisson's ratio (PR) of cement paste can then be predicted using this model by conducting virtual experiments. The simulation results suggest that time-dependent dissolution of cement grains generally causes a relaxation resulting in a decrease of the viscoelastic/viscoplastic PR. However, intrinsic calcium silicate hydrate creep deformation causes either time-dependent increases or decreases in the viscoelastic/viscoplastic PR, depending on the mechanical properties of the calcium silicate hydrate and the water to cement mass ratio. The influence from cement grain dissolution on the overall evolution of Poisson's ratio decreases with age, while the influence of intrinsic calcium silicate hydrate relaxation increases with age.